The effect of infusion strength and time on the sensory profile and acceptability of coconut tea from dried male (Cocos nucifera L.) flowers - Timario, Christine Joy G.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The effect of infusion strength and time on the acceptability and sensory attributes of coconut tea produced from dried male Cocos nucifera L. (PCA 15-2 hybrid) flowers were studied. Nine coconut tea samples were prepared using different infusion strengths (1.0, 1.25, 1.5%) and infusion times (2, 6 and 10 min). The dried coconut flowers were also roasted (90 s) to facilitate extraction of its components and enhance the intensity of its attributes. Consumer acceptance test and Spectrum descriptive analysis were conducted to evaluate the acceptability of the samples and to determine its attributes and its intensities. No significant difference was observed among the samples for the acceptability of color, aroma, flavor and its overall acceptability (P>0.05) as determined by Analysis of Variance (ANOVA). The evaluation of the intensity of the aroma and flavor also showed no significant difference for all samples. It was also observed that the treatment done by roasting the flowers was too weak to create significant difference and thus, had minimal effect on the quality of the coconut tea samples. Mean ratings obtained from the descriptive test were very low and no significant difference among the samples for all attributes was also observed (P>0.05). Regression analysis conducted for all sensory tests showed that the infusion strength and time had no significant effect on the attributes and that these were not good predictors of the response variables. Increasing the concentration would provide better results and the use of other coconut palm parts would also be beneficial to obtain a more acceptable product with more intense flavor and sensory attributes.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Coconut -- Philippines; Coconut -- Processing; Coconut tea